Some Fixed Point Theorems for R˜n-Contraction and R˜n-Kannan Mappings in Metric Spaces - Thanatporn Bantaojai; Chatsuda Chanmanee; Patchara Muangkarn; Suanoom, Cholatis (Science & Technology Asia, 2021)
The purpose of this paper is to extend and improve some results concerning of R′-max-Kannan and R′′-Kannan mappings to R˜n-contraction and R˜n Kannan mappings. Second, we establish new mapping, that is a R˜n contraction and R˜n-Kannan mappings. More than that, we prove the results of fixed point for such mappings in metric spaces.